The understanding of halal food awareness among muslims and non-muslims consumers in Summer mall food court, Kota Samarahan, Sarawak/ Nur Affida Sufian & Nur Farhana Osman - Sufian, Nur Affida; Osman, Nur Farhana (2017)
This chapter 1 is categories into several sections where it consists of the chapter review, states about the background of study, the problem statement, discussing on the research objective, identify research question, the scope of study, the significance of study, definition of terms and lastly, the chapter summary. The research is based on the understanding of Halal awareness between Muslim and non-Muslim consumers.